Bamboo houses mitigate the effects of climate change in Pakistan - United Nations Educational, Scientific; Cultural Organization; Zofeen T. Ebrahim (The UNESCO Courier, 2024)
In 2022, heavy monsoon rainfall left a large part of the population homeless in southern Pakistan. Yasmeen Lari, a world-renowned architect, has designed new houses that are flood- and earthquake-resistant while still incorporating traditional bamboo and mud construction techniques.